The Cybersecurity Guide to Governance, Risk, and Compliance - Edwards, Jason; Weaver, Griffin
"Cyber Security Governance & Risk Management is the monitoring of compliance with agreed cyber security policies and the assessment and management of relevant risks. Cybersecurity is a critical concern for modern businesses, and understanding how to navigate it is vital"-- Provided by publisher.